Концептуальні підходи до розуміння процесів антропогенної дестабілізації екологічних систем - Шапар, А.Г.; Міхєєв, О.В. (Вісник НАН України, 2018)
Виходячи з уявлень про екологічну стабільність і механізми природної саморегуляції розглянуто процеси дестабілізації екологічних систем під
впливом антропогенних чинників, обговорено причини їх виникнення та
тенденції розвитку. Схарактеризовано ознаки, які відображують наявність процесу дестабілізації екологічної компоненти складних техноекосистем. Обговорюється необхідність збереження і підтримки еволюційно
вироблених процесів природної саморегуляції як основи для здійснення заходів з відновлення та оптимізації дестабілізованих екосистем. Вирішення
цих проблем має стати пріоритетним завданням у розробленні та реалізації стратегій сталого розвитку з метою гармонізації взаємодій техно- і біосфери в межах раціонального (екологічно спрямованого) природокористування. The problems of ecological systems destabilization under the influence of anthropogenic factors in the process of economic
use of natural resources are considered. Based on the notions of ecological stability and the mechanisms of natural
self-regulation, the essence of the processes of ecosystems destabilization is analyzed, the reasons for their emergence and
the development tendencies are discussed. The signs reflecting the presence of the destabilizing process of the ecological
component of complex techno-ecosystems are determined. A system of criteria is proposed to establish indicators of
destabilization, which are the results of various changes in the structural and functional organization of ecosystems. The
necessity of preserving and maintaining the evolved processes of natural self-regulation as a condition for the stable
functioning of complex techno-ecosystems and the basis for carrying out measures for restoring and optimizing of destabilized
ecosystems is discussed. The solution of these problems should be considered as a priority task in the development
and implementation of sustainable development strategies with the aim of harmonizing the interaction of the techno- and
biosphere within the framework of rational nature management.